Positron emission tomography in diagnosis and follow-up of treatment of head and neck tumours. Our initial experience - Piętka, Tomasz; Dziuk, Mirosław; Krzymański, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2011)
Introduction: Positron emission tomography/computed tomography (PET-CT) is one of the modalities that allow for imaging the metabolism of human cells. One of the indications for PET-CT is head and neck cancer staging and restaging. Aim of study : To test the diagnostic performance of PET-CT in a single centre study for head and neck cancer patients. Materials and methods : The study involved 60 patients with head and neck cancer diagnosed and treated in our department during 2008-2010. There were 71 PET-CT examinations (in 11 patients multiple studies were performed). In 40 patients PET-CT was performed for pre-operative staging, mainly to assess the presence of lymph node metastases. In 23 cases PET-CT was performed to confirm clinical suspicion of tumour recurrence. In 8 patients, the examination was performed to find the origin of the unknown primary cancer. Results : Positron emission tomography/computed tomography results were compared with conventional imaging modalities and histopathology. In the surgical treatment group 4 false positive findings after histological examination were detected. PET-CT in 2 patients failed to show metastasis to the regional lymph nodes (false negative report). In patients with suspected recurrent tumour the diagnosis was confirmed in 14 cases. In all patients with metastases from an unknown primary origin, PET-CT was positive (4 cases were confirmed clinically). The results of PET-CT studies helped to change the method of treatment in 21 cases. Conclusion : Positron emission tomography/computed tomography may be a valuable tool in detecting, staging and monitoring of selected patients with head and neck cancer, with a significant impact on clinical decision making.